2014
DOI: 10.1177/0143831x14538527
|View full text |Cite
|
Sign up to set email alerts
|

Representation without co-determination? Participation and co-determination for semi-professional shop stewards in the collective participation system in Denmark

Abstract: This article examines co-determination in the collective participation system in Denmark among semi-professional shop stewards and health and safety representatives in the private and the public sector. Union strategies for democratization of working life and economic democracy are no longer progressing as in the 1970s, and co-determination seems to be on the defensive, challenged by new forms of employer strategies, New Public Management principles and the neoliberal strategy for individualization. These deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
0
6
0
8
Order By: Relevance
“…I internasjonal fagforeningsforskning er det stor oppmerksomhet rundt potensialet som ligger i samarbeid og partnerskap mellom arbeidsgivere og arbeidstakere, både for å sikre arbeidstakerinnflytelse og bidra til innovasjon (e.g. Payne, 2017;Caraker et al, 2016;Høyrup, 2010;Hyman, 2002). Internasjonalt er det saerlig fornyet oppmerksomhet rundt laererfagforeningers rolle i utvikling av kvalitet og profesjonalitet i offentlig utdanningbåde nasjonalt og lokalt (e.g.…”
Section: Innledningunclassified
See 1 more Smart Citation
“…I internasjonal fagforeningsforskning er det stor oppmerksomhet rundt potensialet som ligger i samarbeid og partnerskap mellom arbeidsgivere og arbeidstakere, både for å sikre arbeidstakerinnflytelse og bidra til innovasjon (e.g. Payne, 2017;Caraker et al, 2016;Høyrup, 2010;Hyman, 2002). Internasjonalt er det saerlig fornyet oppmerksomhet rundt laererfagforeningers rolle i utvikling av kvalitet og profesjonalitet i offentlig utdanningbåde nasjonalt og lokalt (e.g.…”
Section: Innledningunclassified
“…This is an open access article distributed under the terms of the Creative Commons CC-BY-NC 4.0 License (http://creativecommons.org/licenses/by-nc/4.0/). det faktum at mange offentlig ansatte har en saerlig motivasjon for å bidra til offentlig velferd (Caraker et al, 2016;Knudsen et al, 2011).…”
Section: Diskusjonunclassified
“…This article investigates how unions in the public sector relate to this issue. Common explanations for the lack of democratic employee participation in workplaces typically highlight governance trends, such as New Public Management (NPM), and new forms of employer or management strategies (e.g., Caraker et al, 2016). Another perspective on the role of unions in contemporary societies argues that the influence of unions is fundamentally dependent on how they engage in a "battle of ideas" (George, 1997;Hyman and Gumbrell-McCormick, 2010), and specifically focuses on union strategies related to employee representation and participation (Hyman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, theoretical deliberations on the agenda of collective representation (e.g., Hyman, 1997) and research on the outcome of workplace partnerships relation to bipartite cooperation in public sector workplaces. Previous research on employee participation has suggested that unions' demands for codetermination on overall strategic questions have been dissipating for a long time (Caraker, 2016), and that employee participation typically relates to operational rather than tactical and strategic decisions (Knudsen et al 2011, Knudsen, 1995. However, little is known about whether and how this is related to dominant ideas among unions, nor how unions conceive of the relationship between representative participation and knowledge-based workplace development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has defined 'unions' as democratic actors that contribute to balancing power in society and work life (Behrens et al 2004;Heiret 2012); as such, unions have been viewed as agents of power within class struggle, highlighting employee participation in relation to rights, wages, and working conditions (Caraker et al 2016;Knudsen 1995;Knudsen et al 2011). More recent research on union revitalization has highlighted union organization, capacity, and purpose (Fairbrother 2015), the importance of institutional frameworks and external coalitions (Ibsen & Tapia 2017), and the critical role of unions' strategic capabilities and the need to further develop these ( Murray 2017).…”
mentioning
confidence: 99%